An MLH1 haplotype is over-represented on chromosomes carrying an HNPCC predisposing mutation in MLH1. Issue 5 (1st May 2002) - Hutter, P; Wijnen, J; Rey-Berthod, C; Thiffault, I; Verkuijlen, P; Farber, D; Hamel, N; Bapat, B; Thibodeau, S N; Burn, J; Wu, J; MacNamara, E; et al.
Abstract : Background: The mismatch repair gene, MLH1, appears to occur as two main haplotypes at least in white populations. These are referred to as A and G types with reference to the A/G polymorphism at IVS14-19. On the basis of preliminary experimental data, we hypothesised that deviations from the expected frequency of these two haplotypes could exist in carriers of disease associated MLH1 germline mutations. Methods: We assembled a series (n=119) of germline MLH1 mutation carriers in whom phase between the haplotype and the mutation had been conclusively established. Controls, without cancer, were obtained from each contributing centre. Cases and controls were genotyped for the polymorphism in IVS14. Results: Overall, 66 of 119 MLH1 mutations occurred on a G haplotype (55.5%), compared with 315 G haplotypes on 804 control chromosomes (39.2%, p=0.001). The odds ratio (OR) of a mutation occurring on a G rather than an A haplotype was 1.93 (95% CI 1.29 to 2.91). When we compared the haplotype frequencies in mutation bearing chromosomes carried by people of different nationalities with those seen in pooled controls, all groups showed a ratio of A/G haplotypes that was skewed towards G, except the Dutch group. On further analysis of the type of each mutation, it was notable that, compared with control frequencies, deletion and substitution mutations were preferentially represented on the G haplotype (p=0.003 and 0.005, respectively). Conclusion: We have found that disease associated mutations in MLH1 appear to occur more often on one of only two known ancient haplotypes. The underlying reason for this observation is obscure, but it is tempting to suggest a possible role of either distant regulatory sequences or of chromatin structure influencing access to DNA sequence. Alternatively, differential behaviour of otherwise similar haplotypes should be considered as prime areas for further study.